Role of oxides and porosity on high temperature oxidation of liquid fuelled HVOF thermal sprayed Ni50Cr coatings - Song, B.; Bai, M.; Voisey, K.T.; Hussain, Tanvir (Springer, 2017)
High chromium content in Ni50Cr thermally sprayed coatings can generate a dense and protective scale at the surface of coating. Thus, the Ni50Cr coating is widely used in high temperature oxidation and corrosion applications. A commercially available gas atomized Ni50Cr powder was sprayed onto a power plant steel (ASME P92) using a liquid fuelled high velocity oxy-fuel (HVOF) thermal spray with three processing parameters in this study. Microstructure of as-sprayed coatings was examined using oxygen content analysis, mercury intrusion porosimetry (MIP), scanning electron microscope (SEM), Energy-dispersive X-ray spectroscopy (EDX) and X-ray Diffraction (XRD). Short-term air oxidation tests (4 h) of freestanding coatings (without boiler steel substrate) in a thermogravimetric analyser (TGA) at 700 ℃ were performed to obtain the kinetics of oxidation of the as-sprayed coating. Long-term air oxidation tests (100 h) of the coated substrates were performed at same temperature to obtain the oxidation products for further characterization in detail using SEM / EDX and XRD. In all samples, oxides of various morphologies developed on top of the Ni50Cr coatings. Cr₂O₃ was the main oxidation product on the surface of all three coatings. The coating with medium porosity and medium oxygen content has the best high temperature oxidation performance in this study.